2003
DOI: 10.2166/wst.2003.0648
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic digestion of excess activated sludge with ozone pretreatment

Abstract: Source minimization of excess sludge production by economical means can be considered an attractive option to deal with the problem of sludge disposal under strict disposal standards. In this paper long-term operational results for a process that combines the oxidative ozone pretreatment with anaerobic sludge digestion are described. The ozone pretreatment solubilized around 19% and 37% of the solids at 0.015 and 0.05 gO3/gTS ozone dose. The solubilization ratios during ozonation did not show any significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 20 publications
2
46
0
Order By: Relevance
“…The increase of biodegradability with increasing ozone dosage was in accordance with the finding of Goel et al (2003) and Bougrier et al (2006). They found that CH 4 formation increased with increasing ozone dosage.…”
Section: Effect Of Pretreatment Towards Biochemical Methane Potentialsupporting
confidence: 85%
See 1 more Smart Citation
“…The increase of biodegradability with increasing ozone dosage was in accordance with the finding of Goel et al (2003) and Bougrier et al (2006). They found that CH 4 formation increased with increasing ozone dosage.…”
Section: Effect Of Pretreatment Towards Biochemical Methane Potentialsupporting
confidence: 85%
“…The anaerobic digestion has many advantages compare with other methods, namely (1) a relatively low cost, (2) consumes little energy and nutrition, and (3) anaerobic bacteria ability to transform almost all organic substances into methane (Heredia and Garcia 2005). Goel et al (2003) suggested that the anaerobic process was the most important method to reduce the amount of biosludge in the wastewater treatment system. Various researches on anaerobic process were currently focused on different techniques to increase biosludge biodegradability and hydrolisis through pretreatment (Dohanyos et al 2000;Goel et al 2003;Lissens et al 2004;Heredia and Garcia 2005;Bougrier et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ozone is able to convert refractory organic matters into biodegradable form (Volk et al, 1993;Nishijima et al, 2003). Most importantly sludge biodegradability is reported to be remarkably improved after ozonation (Weemaes et al, 2000;Goel et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that 5-26% of TS can be mineralised at ozone dosages of 18-50 mg O 3 /g TSS (Chu et al, 2009b;Goel et al, 2003). Included in this mineralized fraction are the inert or non-biodegradable solids .…”
Section: Mineralisationmentioning
confidence: 99%